KEKUATAN HUKUM PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN - Novreddy Sihombing; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Agency Of Consumer Dispute Resolution is a special court that consumers are expected to answer the demands of the community to litigants process runs fast, simple and cheap to Article 54 Paragraph (3) of BFL, Agency Of Consumer Dispute Resolution decision as a result of the settlement of consumer disputes by conciliation, mediation or arbitration, shall be final and binding . Final sense means that dispute settlement has been completed and ended, while the word connotes binding force and as something that should be undertaken by the parties is required for it. In accordance with the interpretation of Article 54 paragraph (3) of BFL, which referred to the decision of the tribunal is final is that in Agency Of Consumer Dispute Resolution no appeal and cassation. However, in Article 56 Paragraph (2) of BFL mentioned that when consumers or businesses refuse Agency Of Consumer Dispute Resolution decision, may appeal to the District Court and the Supreme Court. This is contrary to the meaning of BPSK decision which is final and binding, with the provisions of the Articles of contradictory and inefficient.In accordance with the above description, the authors are interested in conducting research under the title The Power of Law Consumer Dispute Settlement Body decision. This thesis aims to determine the verdict of Consumer Dispute Settlement Body has the force of law executory, to learn to understand the legal consequences of the decision of the Consumer Dispute Settlement Body that is not practicable, and to mengetahuiupaya which can be reached by the parties to the objection of consumer Dispute Settlement Body decision.In this thesis, the author uses the method of normative legal research. Data sources supported by the data source of primary, secondary and tertiary. While collecting data is literature study and survey data using deductive method is to analyze the problems of a general nature and specifically the conclusions drawn on the basis of existing theories.The results of the discussions in this paper is, first, a decision that can be executed Agency Of Consumer Dispute Resolution. Agency Of Consumer Dispute Resolution decision which contains the amount of indemnity, and does not violate the principle of ultra virus or exceed those specified in Article 178 Paragraph (3) HIR, that decision can not be more than requested in petititum. Second, Entrepreneurs who do not file an objection within the period referred to in Article 56 Paragraph (2) are deemed to accept the decision of Agency Of Consumer Dispute Resolution, when not carried out by carriers, Agency Of Consumer Dispute Resolution submit the decision to the investigator to conduct the investigation in accordance with the statutory provisions applicable. Third, efforts which can be reached by the parties objected to the decision of the Consumer Dispute Settlement Board is to submit objections to the District Court and the Supreme Court. Agency Of Consumer Dispute Resolution objection to the proposed decision to the District Court is included Jurisdiction ContentiosaKeywords: Legal Force, Eexecutorial, Agency Of Consumer Dispute Resolution